Subsurface Defects Evaluation using Eddy Current Testing - Damhuji, Rifai; Abdalla, Ahmed N.; Noraznafulsima, Khamshah; Mohd, Aizat; Mohd, Fadzli (Informatics Publishing Limited, 2016)
Eddy current testing is one of the most widely Non Destructive Evaluation (NDE) methods which utilized in the industry especially in oil and gas, aircraft, nuclear and coating industries. Experimental studies of eddy current testing have emerged as an important approach alongside numerical. This paper is to design, fabricate and investigate the maximum eddy current testing that can detect subsurface defect in the carbon steel S45C block. Methods/Statistical Analysis: The material of the artificial defect block is carbon steel (S45C) with dimension of 180mm (length) × 25mm (width) × 60mm (height). There are eight artificial defects which located 20mm parallel to the length of the block with 0.5mm diameter. The distance defect is located in between 0.5mm to 4.00mm from the surface of the artificial defect block. Weld probe with diameter size of 16mm and 9mm are used to perform the inspection. Findings: Experiments showed that the weld probe with diameter 16mm able to detect subsurface defect up to 4.0mm and 2.0mm for 9mm diameter weld probe. The optimum of eddy current testing frequency for carbon steel S45C is depending on the defect distance from the material surface. Applications/Improvements: The results prove that the maximum depth of the subsurface can be measured by using eddy current testing method, which is depending on the frequency of the exciting coil weld probe.